Fostering students’ critical thinking skill in chemistry through science, technology, society, environment (STSE) collaborative learning - Erfan Priyambodo; Metridewi Primastuti; Nur FItriyana; Hermas Randhanugraha (Jurnal Inovasi Pendidikan IPA, 2021)
Learning activities always develop following the needs of the times. Some skills, such as critical thinking, need to be possessed by 21st-century individuals. This study aims to analyze critical thinking skills of students who learn collaboratively based on the Science, Technology, Society, and Environment (STSE) learning approach. A posttest nonequivalent control group design was adopted in this research. Through cluster random sampling, 68 students at one public senior high school in Sleman Yogyakarta, participated as a research sample, which divided into 2 classes. Students in experimental class (N=35) has been learn about electrolyte nonelectrolyte topic through collaborative learning based STSE approach. While, the other students in the control class (N=34), taught by student center learning. In the fifth meetings, students’ critical thinking skill was measured as a research data through an essay questions instruments that has been empirically validated. Afterwards, research data were analyzed using independent sample t-test. Moreover, the p-value shown in the analysis results was 0.009. This result is sufficient to indicate that at the 95% confidence level there is a significant difference in students' critical thinking skill between the experimental class and the control class. The partial eta squared value shows that STSE learning approach has an effect to fostering students’ critical thinking in learning chemistry, in this research there was 9.8% effect that can be highlighted.